edited by
925 views
1 votes
1 votes
If $\left(\sqrt{\frac{7}{3}}\right)^{2 x-y}=\frac{875}{2401}$ and $\left(\frac{4 a}{b}\right)^{4 x-y}=\left(\frac{2 a}{b}\right)^{y-6 x}$, for all non-zero real values of $a$ and $b$, then the value of $x+y$ is
edited by

1 Answer

0 votes
0 votes

1st equation :- ($\sqrt{7/5}$)$^{3x-y}$ = 875/2401 = 125/343 = 5$^{3}$/7$^{3}$

=> (7/5)$^{(3x-y)/2}$ = (7/5)$^{-3}$  => (3x – y)/2 = -3  => y = 3x + 6

2nd equation :- (4a/b)$^{6x-y}$ = (2a/b)$^{y-6x}$  => 2$^{12x-2y}$ x a$^{6x-y}$ x b$^{-6x+y}$ = 2$^{y-6x}$ x a$^{y-6x}$ x b$^{6x-y}$

=> 2$^{18x-3y}$ x a$^{12x-2y}$ = b$^{12x-2y}$  => (8a$^{2}$/b$^{2}$)$^{6x-y}$ = 1

In this equation if (8a$^{2}$/b$^{2}$) != 1, then we can say that 6x-y=0. Since the only info given for a & b is that it is non zero real number and from this we can’t derive that (8a$^{2}$/b$^{2}$) != 1. But for solving this question we need another equation in terms of x & y. So, assume (8a$^{2}$/b$^{2}$) != 1. Then we can say y = 6x.

After solving y = 3x + 6 and y = 6x, we get x = 2 and y = 12.

Ans is x+y=14.

Answer:

Related questions

1 votes
1 votes
1 answer
1
1 votes
1 votes
1 answer
2
admin asked Mar 3, 2023
1,759 views
If $c=\dfrac{16 x}{y}+\dfrac{49 y}{x}$ for some non-zero real numbers $x$ and $y,$ then $c$ cannot take the value$-60$ $-50$ $60$ $-70$
2 votes
2 votes
1 answer
3
admin asked Mar 3, 2023
402 views
If $(3+2 \sqrt{2})$ is a root of the equation $a x^{2}+b x+c-0$, and $(4+2 \sqrt{3})$ is a root of the equation $a y^{2}+m y+n – 0$, where $a, b, c, m$ and $n$ are inte...
1 votes
1 votes
0 answers
4
admin asked Mar 3, 2023
315 views
Suppose the medians $\mathrm{BD}$ and $\mathrm{CE}$ of a triangle $\mathrm{ABC}$ intersect at a point $\mathrm{O}$. If area of triangle $\mathrm{ABC}$ is $108$ $\mathrm{s...